Wave-Based Substructuring Method for Dynamic Behaviour Investigation of Solid Meshing Based Finite Element Model of a Structure / Ahmad Burhani Ahmad Basri ... [et al.] - Ahmad Basri, Ahmad Burhani; Abdul Rani, Muhamad Norhisham; Yunus, Mohd Azmi; Wan Iskandar Mirza, Wan Imaan Izhan; Abu Samah, Siti Akmar (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The significant advantage of using solid meshing for the development of the FE model of a structure is that the structure can be modelled without any priori geometric simplification. This provides a higher accuracy of finite element model in comparison with the beam and shell meshing element. However, 3D or solid meshing usually creates an unfavourable way of modelling especially when it comes to modelling a large complex engineering structure. This paper puts forward the idea of using wave-based substructuring (WBS) to investigate the dynamic behaviour of the solid meshing based FE model of a structure with a large number of interface DOFs. The finite element method was used to construct the full finite element model of the structure and NASTRAN 103 was then used for the normal modes analysis. A new finite element model of the structure with reduced interface DOFs was constructed based on the WBS method. The measurement of the dynamic behaviour of the structure was carried out using free-free boundary conditions and an impact hammer test. The predicted results of the proposed method are then compared with those from the full finite element model and experimental counterparts. It was found that the recommended relative threshold value to be use for Singular Value Decomposition (SVD) in 3D modelling is 1e-6. The comparisons of the results between the full FE, WBS method and test models revealed that the use of WBS method has led to a dramatic reduction in the expenditure of computational time by 80% faster than the full FEM while still maintaining a satisfactory level of accuracy. This indicates that the WBS method can be used economically and efficiently for the determination of dynamic behaviour of a solid meshing based finite element model.